Design of concrete structures - Nilson, Arthur H., Prof. (McGraw-Hill civil engineering series / McGraw-Hill series in construction engineering and project management., 1997)
Introduction; Materials; Flexural analysis and design of Beams; Shear and diagonal tension in beams; Bond, anchorage, and development length; Serviceability; Analysis and design for torsion; ..